Tip of an iceberg : anti-lesbian and anti-gay discrimination in Europe 1980-1990: a survey of discrimination and anti-discrimination in law and society - Waaldijk, Kees (Utrecht : International Lesbian and Gay Association Department of Gay and Lesbian Studies, university of Utrecht, 1991)
Fonds Suzan Daniel - FSD
Engels
Monografie